EjBZR1 represses fruit enlargement by binding to the EjCYP90 promoter in loquat. (1st July 2021) - Su, Wenbing; Shao, Zikun; Wang, Man; Gan, Xiaoqing; Yang, Xianghui; Lin, Shunquan
Abstract: Loquat ( Eriobotrya japonica ) is a subtropical tree that bears fruit that ripens during late spring. Fruit size is one of the dominant factors inhibiting the large-scale production of this fruit crop. To date, little is known about fruit size regulation. In this study, we first discovered that cell size is more important to fruit size than cell number in loquat and that the expression of the EjBZR1 gene is negatively correlated with cell and fruit size. Virus-induced gene silencing (VIGS) of EjBZR1 led to larger cells and fruits in loquat, while its overexpression reduced cell and plant size in Arabidopsis . Moreover, both the suppression and overexpression of EjBZR1 inhibited the expression of brassinosteroid (BR) biosynthesis genes, especially that of EjCYP90A . Further experiments indicated that EjCYP90A, a cytochrome P450 gene, is a fruit growth activator, while EjBZR1 binds to the BRRE (CGTGTG) motif of the EjCYP90A promoter to repress its expression and fruit cell enlargement. Overall, our results demonstrate a possible pathway by which EjBZR1 directly targets EjCYP90A and thereby affects BR biosynthesis, which influences cell expansion and, consequently, fruit size. These findings help to elucidate the molecular functions of BZR1 in fruit growth and thus highlight a useful genetic improvement that can lead to increased crop yields by repressing gene expression.